Ironic negatives in isiXhosa - Slater, Onelisa Mellesa (Rhodes University, 2026)
This thesis examines the morphopragmatics of negation in isiXhosa and observes that negative constructions can also be interpreted as emphasizing the affirmative – a phenomenon referred to as ‘ironic negation’. This phenomenon suggests that negative morphology yields ambiguous structures in the language (Oosthuysen 2016). Upon closer investigation of the data, this thesis reveals that linguistic constructions that contain negative morphology split into three categories: (i) unambiguous negative constructions, (ii) ambiguous negative between negative and ironic negative (Oosthuysen 2016), and (iii) unambiguous ironic negative construction. The data for this study was obtained from (a) questionnaires administered to 30 native isiXhosa speakers who provided intuitive judgements about the meanings of negative constructions, (b) listening tasks in which native speakers interpreted the meanings of the negative constructions, and (c) an audio recording task in which speakers read out a negative construction with a particular meaning in mind. Using a Chi-square test in the statistical program R and Praat analysis of the data, the study found that the interpretation of negative expressions is determined by the TAM in which the expression occurs, type of predicate that is negated, and the tone of the utterance.
Keywords: Uncatalogued